2022
DOI: 10.3390/agriculture12030390
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs Assessment: The Case of Female Rice Farmers in Northern Iran

Abstract: An appraisal of training requirements responds to the issue of why training is needed and gives some assurance that the services needed to establish and conduct training can achieve the required outcomes based on performance. Therefore, the goal of this study was to examine the educational needs of female rice farmers in Sari (the capital of Mazandaran province located in Northern Iran). This study adopted a descriptive-correlational approach consisting of 1677 female rice farmers in Sari in 2013–2015. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Education is considered an essential factor in reducing the training of the farmers in tilapia culture. These results are consistent with those of previous investigations (Pandit and Basak, 2014;Mohamed et al, 2020;Goli et al, 2022), which revealed that farmers with lower education need more training.…”
Section: Level Of Educationsupporting
confidence: 94%
“…Education is considered an essential factor in reducing the training of the farmers in tilapia culture. These results are consistent with those of previous investigations (Pandit and Basak, 2014;Mohamed et al, 2020;Goli et al, 2022), which revealed that farmers with lower education need more training.…”
Section: Level Of Educationsupporting
confidence: 94%
“…There are also studies that have indicated that agricultural skills training cannot make farmers fully understand agricultural knowledge, with no knowledge spillover [32,39]. In addition, agricultural skills training is also affected by training methods, training environment, and farmers' personal characteristics [18,[40][41][42]. As a kind of agricultural skills training, agricultural machinery maintenance training is conducive to the maintenance of agricultural machinery equipment and normal operation.…”
Section: Research On Skills Trainingmentioning
confidence: 99%